Texting Older Sisters to Step: The TOSS Study. (March 2019) - Bowen, Pamela G.; Clay, Olivio J.; Lee, Loretta T.; Browning, Wesley; Schoenberger, Yu-Mei; Martin, Michelle Y.
The purpose of our two-phase study was to develop acceptable text messages to increase physical activity. Four focus groups (two for each phase) were conducted with older African American women who had access to texting-capable mobile phones and were in the contemplation stage for physical activity. The mean age of Phase 1 participants ( n = 12) was 71 and ranged from 65 to 86 years. Content analysis was used to identify fundamental themes that were later used to develop text messages. Six categories emerged from the data and 31 text messages were developed based on focus group input and national recommendations. The mean age of Phase 2 participants ( n = 9) was 67 and ranged from 65 to 75 years. Descriptive statistics revealed 100% of participants understood all messages. When messages were evaluated individually, a minimum of 78% felt each message motivated activity and 67% said lengths were perfect. Findings identified messages that were relevant and potentially motivational to stimulate physical activity among this population.